Peran Badan Usaha Milik Desa (Bumdes) Dalam Pemberdayaan Ekonomi Masyarakat Di Desa Mas-Mas Kecamatan Batukliang Utara Kabupaten Lombok Tengah - Muhammad Zainul Majdi; Susilawati Susilawati; Farhana Muhammad; Nurhastuti Nurhastuti (Universitas Hamzanwadi, 2020)
This study aims to know the role of Village-Owned Enterprises (BUMDES) in society economic empowerment at Mas-mas Village, Batukliang Utara District, and Central Lombok Regency. This study was descriptive qualitative approach. The study was conducted from June to July at Mas-Mas Village, Batukliang Utara, and Central Lombok. The data collection techniques used interview, documentation, and observation with study subjects, namely the Head of Village, BUMDES management and some society of Mas-mas. The researcher used techniques of source triangulation. Data analysis in this study uses an interactive analysis model that is analysis using data reduction, data presentation, and verification and conclusions. The results of this study indicated that the role of BUMDES Lintang Mas had not been maximized in society economic empowerment at society of Mas-mas Village; it can be seen from the types of businesses run by BUMDES. In addition, the level of society participation was still low.